Global, regional, and national estimates of pneumonia morbidity and mortality in children younger than 5 years between 2000 and 2015: a systematic analysis - David A McAllister, MD; Li Liu, PhD; Ting Shi, PhD; Yue Chu, MSPH; Craig Reed, PhD; John Burrows, MBChB; Davies Adeloye, PhD; Igor Rudan, ProfPhD; Robert E Black, ProfMD; Harry Campbell, ProfMD; Harish Nair, ProfPhD (Elsevier, 2019)
Summary: Background: Global child mortality reduced substantially during the Millennium Development Goal period (2000-15). We aimed to estimate morbidity, mortality, and prevalence of risk factors for child pneumonia at the global, regional, and national level for developing countries for the Millennium Development Goal period. Methods: We estimated the incidence, number of hospital admissions, and in-hospital mortality due to all-cause clinical pneumonia in children younger than 5 years in developing countries at 5-year intervals during the Millennium Development Goal period (2000-15) using data from a systematic review and Poisson regression. We estimated the incidence and number of cases of clinical pneumonia, and the pneumonia burden attributable to HIV for 132 developing countries using a risk-factor-based model that used Demographic and Health Survey data on prevalence of the various risk factors for child pneumonia. We also estimated pneumonia mortality in young children using data from multicause models based on vital registration and verbal autopsy. Findings: Globally, the number of episodes of clinical pneumonia in young children decreased by 22% from 178 million (95% uncertainty interval [UI] 110-289) in 2000 to 138 million (86-226) in 2015. In 2015, India, Nigeria, Indonesia, Pakistan, and China contributed to more than 54% of all global pneumonia cases, with 32% of the global burden from India alone. Between 2000 and 2015, the burden of clinical pneumonia attributable to HIV decreased by 45%. Between 2000 and 2015, global hospital admissions for child pneumonia increased by 2·9 times with a more rapid increase observed in the WHO South-East Asia Region than the African Region. Pneumonia deaths in this age group decreased from 1·7 million (95% UI 1·7-2·0) in 2000 to 0·9 million (0·8-1·1) in 2015. In 2015, 49% of global pneumonia deaths occurred in India, Nigeria, Pakistan, Democratic Republic of the Congo, and Ethiopia collectively. All key risk factors for child pneumonia (non-exclusive breastfeeding, crowding, malnutrition, indoor air pollution, incomplete immunisation, and paediatric HIV), with the exception of low birthweight, decreased across all regions between 2000 and 2015. Interpretation: Globally, the incidence of child pneumonia decreased by 30% and mortality decreased by 51% during the Millennium Development Goal period. These reductions are consistent with the decrease in the prevalence of some of the key risk factors for pneumonia, increasing socioeconomic development and preventive interventions, improved access to care, and quality of care in hospitals. However, intersectoral action is required to improve socioeconomic conditions and increase coverage of interventions targeting risk factors for child pneumonia to accelerate decline in pneumonia mortality and achieve the Sustainable Development Goals for health by 2030. Funding: Bill & Melinda Gates Foundation.